The tolerability of Potassium Citrate Tablet in patients with intolerance to Potassium Citrate Powder form - Basiri, Abbas; Taheri, Fatemeh; Taheri, Maryam (Urology Journal, 2018)
Purpose: To assess the tolerability of Potassium Citrate (KCit) tablets in patients with kidney stones that were not able to use the powder form of this drug due to unfavorable salty taste and /or gastrointestinal complications. Materials and Methods: Twenty-three stone formers, with intolerance to potassium citrate powder form, which had referred to Labbafinejad stone preventive clinic in 2015, were included in this study. All of the patients took two potassium citrate tablets (10 meq), three times a day for two weeks. Spot urine samples and the 24-hour urine collections were performed before and after KCit therapy. In addition, a visual analog taste scale was completed to gauge the taste and palatability of the KCit tablets in comparison with the powder form. Results: All of the patients claimed that they consumed the tablets as prescribed. The urine pH (5.7 ± 0.6 to 6.1 ± 0.8, p = 0.006), 24-hour citrate (235.8 ± 190.2 to 482.5 ± 323.2, p = 0.0002) and potassium (45.25 ± 22.5 to 75.27 ± 37, p = 0.002) were significantly higher after the treatment. In addition, the mean visual analog scale score was significantly improved in KCit therapy with tablet form versus to powder form of the drug (good vs. terrible score). Conclusion: Oral tolerance of KCit therapy is improved with the use of Potassium Citrate tablet, with beneficial effects on 24-hour urine citrate, potassium, and pH.